Restricting loans of money to Hong Kong civil servants: social censure or violation of human rights? - Lo, Tit Wing (Crime, law and social change, 2009)
Obtaining a loan is an individual’s private business and such a right should be free from interference. However, if Government officers obtain a loan from undesirable persons, they may be lured into committing an act which they would not otherwise have done but for the favours having been shown by the lenders. Section 3 of Hong Kong’s Prevention of Bribery Ordinance attempts to limit such behaviour of Government officers. Since the power of this provision is draconian, it may possibly violate human rights. This paper attempts to use a Social Censure perspective to explain why this provision was put in place in the 1970s and why it was not repealed in the 1990s in line with the rise of human rights standards in Hong Kong. It argues that the then British colonial government used a high-hand legal code to fight against corruption in the civil service to win its legitimacy in face of the rise of Red China in the 1970s. A review of twenty-one Section 3 cases suggests that most of the loans were not distributed for mere friendship but involved a wide range of culpability. Thus the coercion generated by Section 3 was approved by the masses, resulting in the reinforcement of a draconian but efficient legal provision in the service of the colonial administration.